Pengaruh Kecerdasan Emosional Terhadap Konsentrasi Belajar Siswa Mata Pelajaran Pendidikan Agama Islam SMA Negeri 2 Tapung Tapung - Maulani, Alya (CV Najmi Edu Creative, 2025)
This study was motivated by the low concentration of students' learning at SMA Negeri 2 Tapung, which is characterized by a lack of concentration, readiness to learn, and interest and motivation in participating in learning. This study aimed to determine the effect of emotional intelligence on students' learning concentration in Islamic Religious Education subjects. This study used a quantitative approach with a correlational method. The research sample was determined using the Slovin formula with a margin of error of 5% from a population of 153 students in grades X and XI; a sample of 110 students was obtained. The data collection techniques used were questionnaires and documentation. Data analysis was carried out through normality tests, linearity tests, and hypothesis tests. The results showed a significant influence between emotional intelligence and students' learning concentration, with a significance value of 0.001 (p <0.05). The magnitude of the influence of emotional intelligence on students' learning concentration was 56.8%, which was included in the moderate category. Thus, emotional intelligence significantly influences students' learning concentration in Islamic Religious Education subjects at SMA Negeri 2 Tapung.